Strategies for the treatment of AIDS-associated sclerosing cholangitis - Velásquez, Jorge Néstor (2004)
Fil: Velásquez, Jorge. Hospital Municipal de Infecciosas “Dr. Francisco J. Muñiz” Buenos Aires; Argentina.